EFFEC OF SALT STRESS ON YIELD AND ITS COMPONENTS OF FOUR CULTIVARS OF BARLER - Mutlag, Naeem. A.; Mohammed, Aliaa. K. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
A field experiment was carried out at the field with clay loam soil in the winter seasons of 2018 - 2019 and 2019 - 2020 in order to study the effect of three levels of salt stress on yield and its components for four cultivars of barley (Hordeum valgare L.(. which be approved in Iraq.Factorial experiment with in Randomized Complete Block design with three replications. The treatments included three levels of irrigation water salinity (5,10,15) ds.m-1 and four cultivars of barley (IPA 99, Buhooth 265, Samir, and Amal). The results showed that the salinity of the irrigation water caused a significant decreases of the number of spikes.m-2, number of grains. spike-1, weight of 1000 grains (gm) and grain yield. plant. -1 at levels S2 and S3 and for both studies seasons in comparison with treatment S1, which gave the highest averages for the mentioned traits, significant differences among barley cultivars in terms of their tolerance to salinity. It was found that Samir cultivar was more tolerant to salinity than the other cultivars.